Taxing wages. 2009-2010. Special feature: wage income tax reforms and changes in tax burdens: 2000-2009 (Paris, 2011)
"Taxing Wages provides information on income tax paid by workers and social security contributions levied on employees and their employers in OECD countries. Calculations also include family benefits paid as cash transfers. Data are provided for different income levels and household types. Results include the average and marginal effective tax burden on employees and the total labour costs of employers. A special feature from the current edition looks into wage income tax reforms and changes in tax burdens during the 2000-2009 period."